Landscape's Revenge : the ecology of failure in Robert Walser and Bernardo Carvalho - Yurgel, Caio (Latin American Literatures in the World / Literaturas Latinoamericanas en el Mundo ;, 2019)
Landscape, as it appears and is described throughout the works of Bernardo Carvalho and Robert Walser, provides an excellent-yet virtually unexplored-pathway to the authors' literary projects. The landscape functions here as a synthetic and unifying figure that triggers, at first, through the analysis of its description per se, the main and most evident elements of the authors' works. However, when sustained as a methodological figure beyond the scope of its own description, the landscape soon reveals a darker, far more fascinating and far less explored side of the authors' oeuvres: a vengeful, seemingly defeatist resentment against the status quo, which gives way to the more latent and biting elements of the authors' prose, such as irony, the unheimlich, an anti-heroic agenda, the apocalyptic aesthetics of a disaster-prone fictional world, as well as an understanding of history and literature through the figures of failure and marginality. By drawing from diverse critical traditions from Latin-America and Europe, this comparative text seeks to unravel, in all of its complexity and scope, the fictional stage upon which Walser's and Carvalho's characters narrate, with their dying breath, a world that is slowly undoing itself.